2002
DOI: 10.1021/jm011056m
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry at Phosphorus of the Reaction Catalyzed by myo-Inositol Monophosphatase

Abstract: myo-Inositol monophosphatase (IMPase), the proposed target for lithium therapy for manic depression, is an important enzyme in the biosynthesis of second messengers. Earlier studies have shown that the IMPase-catalyzed hydrolysis of myo-inositol monophosphates to inorganic phosphate and myo-inositol proceeds by direct attack of water at phosphorus. However, research groups have independently proposed either an in-line displacement (with inversion of stereochemistry at phosphorus) or an adjacent attack with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 52 publications
(239 reference statements)
0
3
0
Order By: Relevance
“…IMPase requires magnesium ions (Mg 2+ ) as a cofactor, ,,,,, and the maximum catalytic activity is seen at a Mg 2+ ion concentration of 3–4 mM, while higher concentrations result in an uncompetitive inhibition of the enzyme . Several mechanisms have been proposed to explain the IMPase reaction, such as the ping-pong mechanism that proceeds through a phosphoenzyme intermediate, , the noninline displacement mechanism that is accompanied by pseudorotation, , and the inline or S N 2 displacement that results in inversion of the configuration around phosphorus. , The current consensus is that the reaction proceeds via inline displacement, as this mechanism is consistent with the experimental configuration analysis using oxygen isotopes. , This inline mechanism involves the initial activation of a water molecule by a nearby Mg 2+ ion at the metal-binding site 1 (M1 in Figure ) to produce a hydroxide ion. The hydroxide then attacks the phosphorus in an S N 2 fashion to release the hydrolysis products, MI, and inorganic phosphate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMPase requires magnesium ions (Mg 2+ ) as a cofactor, ,,,,, and the maximum catalytic activity is seen at a Mg 2+ ion concentration of 3–4 mM, while higher concentrations result in an uncompetitive inhibition of the enzyme . Several mechanisms have been proposed to explain the IMPase reaction, such as the ping-pong mechanism that proceeds through a phosphoenzyme intermediate, , the noninline displacement mechanism that is accompanied by pseudorotation, , and the inline or S N 2 displacement that results in inversion of the configuration around phosphorus. , The current consensus is that the reaction proceeds via inline displacement, as this mechanism is consistent with the experimental configuration analysis using oxygen isotopes. , This inline mechanism involves the initial activation of a water molecule by a nearby Mg 2+ ion at the metal-binding site 1 (M1 in Figure ) to produce a hydroxide ion. The hydroxide then attacks the phosphorus in an S N 2 fashion to release the hydrolysis products, MI, and inorganic phosphate.…”
Section: Introductionmentioning
confidence: 99%
“…41,79−81 The current consensus is that the reaction proceeds via inline displacement, as this mechanism is consistent with the experimental configuration analysis using oxygen isotopes. 82,83 This inline mechanism involves the initial activation of a water molecule by a nearby Mg 2+ ion at the metal-binding site 1 (M1 in Figure 1) to produce a hydroxide ion. The hydroxide then attacks the phosphorus in an S N 2 fashion to release the hydrolysis products, MI, and inorganic phosphate.…”
mentioning
confidence: 99%
“…Ins(2)P 1 is hydrolyzed by myo -inositol monophosphatase (IMP) in the metabolic pathway of inositol phosphates in living systems . The conformation of Ins(2)P 1 is essential to understanding the mechanism of IMP which has been a subject of recent experimental research. NMR investigations have shown that higher inositol phosphates can adopt either the 5a/1e or 1a/5e conformations which readily interconvert through ring inversion, the ease of which is dependent on the pH. , For example, myo -inositol hexakisdihydrogenphoshate, i.e., phytic acid, and some myo -inositol pentakisdihydrogenphosphates (such as Ins(1,2,3,4,6)P 5 and Ins(,2,3,5,6)P 5 ) adopt the 1a/5e conformation in the pH range below 9.0 but the sterically hindered 5a/1e conformation above pH 9.5 (Figure ). More importantly, inositol phosphates are models for compounds having both hydroxyl (−OH) and phosphate groups such as RNAs, nucleotides, and phosphorylated sugars.…”
Section: Introductionmentioning
confidence: 99%